Avaliação Pós-Ocupação do Conjunto Residencial Gervásio Maia - PB - Vale, Kátia Cristina do (2012)
The right to housing is not restricted to possession of a dwelling unit, it includes the right to quality of life through access to leisure and culture, urban infrastructure, goods and services, security, health, education and work. In this context, the neighborhood Gervasio Mayan, located in the southwest of the city of Joao Pessoa in Paraiba, was chosen as an object of study by entering into the government program to eradicate the country's housing deficit. The set houses low-income families enrolled in the program of assistance to housing the City of João Pessoa. The work consists in evaluating post-occupancy (APO Avaliação Pós-Ocupação) of that set, aiming to characterize this population access to leisure and culture, urban infrastructure, goods and services, security, health, education and work, through desk research, site visits and questionnaires. The questionnaires were administered on site, with users of 100 housing units, randomly distributed throughout the neighborhood. The main results are: a) high pass on the benefit to others homes, b) low security - perceived by the predominance of high walls and installation of guardrails d) reduced mobility due to low supply of public transport and the cost of tickets, variable that affects access to leisure and culture (nonexistent on site), as well as labor, goods and services, e) poor lighting and lack of mail service.